Daniyal Mueenuddin Talking Back - Mudure, Mihaela (AMERICANA E-journal of American Studies in Hungary, 2021)
“Writing back”, the famous post-colonial strategy theorized by Ashcroft, Griffiths, and Tiffin, is not able enough to grasp the characteristics of Daniyal Mueenuddin’s literary discourse in his first book: the short story cycle In Other Rooms, Other Wonders. After an evaluation of the “talking back” formula and the re-writing formula, I have come to the conclusion that the former is a better tool in order to understand the modalities in which the American and the Pakistani cultures influenced Daniyal Mueenuddin’s literary personality, his way of talking back to the environments that shaped and in-formed his personality. Talking back to the world, Daniyal Mueenuddin proves to be a very significant personality of the Global South and of the world we live in, a world where cultures, individuals meet and talk to each other more than in any other previous age. Daniyal Mueenuddin’s writing is significant for the contemporary world conversation.